Online Shopping Experience and Repurchase Intention in Beauty and Personal Care in Pontianak City: The Mediating Role of Trust - Sumiyati Sumiyati; Neni Triana M (Economics and Business Journal (ECBIS), 2026)
The rapid growth of e-commerce has increased the importance of understanding factors that influence consumer repurchase intention, particularly in the beauty and personal care product sector. This study aims to analyze the effect of customer online shopping experience on repurchase intention with trust as a mediating variable among beauty and personal care product consumers in Pontianak City. This research employs a quantitative associative approach with a sample of 175 respondents selected through purposive sampling. Data were collected using questionnaire with Likert-scale (1–4) and analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results indicate that: (1) online shopping experience has a significant effect on trust (t-statistics 6,235; p values 0.000); (2) online shopping experience has a significant effect on repurchase intention (t-statistics 5,395; p values 0.000); (3) trust has a significant effect on repurchase intention (t-statistics 4,680; p values 0.000); and (4) trust mediates the effect of online shopping experience on repurchase intention (t-statistics 4,397; p values 0.000). These findings suggest that a positive online shopping experience and consumer trust are key factors in driving repurchase intention for beauty and personal care products through e-commerce platforms.